Political game theory: An introduction - McCarty, Nolan M (Cambridge University, 2013)
Political Game Theory is a self-contained introduction to game theory and its applications to political science. The book presents choice theory, social choice theory, static and dynamic games of complete information, static and dynamic games of incomplete information, repeated games, bargaining theory, mechanism design, and a mathematical appendix covering logic, real analysis, calculus, and probability theory. The methods employed have many applications in various subdisciplines including comparative politics, international relations, and American politics. Political Game Theory is tailored to students without extensive backgrounds in mathematics and traditional economics; however, many special sections present technical material appropriate for more advanced students. A large number of exercises are also provided for practice with the skills and techniques discussed.